MENGEMBANGKAN INTELIGENSI DAN KREATIVITAS ANAK USIA DINI - M. Zaqin (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
There are two reasons why intellegence and creativity of pre school children need to be developed? First of all, it is related to the development and the growth of children. Secondly, it is related to the demand of society development. Learning has important role in developing intellegence and creativity of pre school children. Learning which is considered able to develop intellegence and creativity and to develop children’s right and left brain is the learning suitable to the principle of pre school children education. Centre is one of the ways to manage class whose teaching-learning process consists of related and integrated centres based on fully and appropriately need of children. Centre can be developed by institution in accordance with the competence of educators, staffs of education and the facilities. In general, there are at least four centres Pre school (PAUD) institutions must develop. They are; Balok centre, role play (main peran) centre, natural things (bahan alam) centre and preparation centre.